Necesidad de estipular en el código penal Ecuatoriano, en el libro II, título VIII; los delitos de pedofilia y pederastia, a fin de tener una normativa que ayude a reducir el índice de abuso sexual a menores - MOROCHO P., HENRY F. (2010)
Sexual crimes are an affront against sexual freedom and indemnity of each individual classification is typified in the Ecuadorian Criminal Code, in Book II, Title VIII, and since the sexual assault against children under fourteen years the focus of the this has been analyzed and reviewed information concerning pedophilia and pederasty from ancient times until today. Taking into account the personality and behavior of pedophiles and pedophile offenders clearly that this is deductible for individuals with serious psychological and social, that the bank to commit such heinous acts. Our Penal Laws, in their arts. 512 to 515 presents the rules inherent to the crime of rape, but this legislation becomes insufficient when talking about victims under fourteen years because no one takes into account the emotional and physical damage that abuse has on victims. The penalty for the crime of child molestation in our country as well as in some countries with similar social, political, cultural and underdevelopment as ours, we suggest that the Ecuadorian penal system is failing, failing to take into account pedophilia and child molestation offenses, this would serve as an alternative to protect the integrity and sexual indemnity under fourteen years, for this reason this research work is directed at reforming the penal code to include these two actions (pedophilia and pederasty) as crimes, establishing severe penalties for those actively involved in this most reprehensible act.